Earnings Management: Legal Vs Unethical - Nelwan, Melinda Lydia (JBE (Journal of Business and Economics); Volume 8 No.2, 2009 JBE UNKLAB, 2009)
The obligation to perform good financial reports sometimes puts pressure on managers and/or accountants to meet the needs that leads to engage in earnings management practices, which are companies’ actions in modifying their income.  Earnings management could be conducted legally according to Generally Accepted Accounting Principles (GAAP), but to some extent carries out in unethical way.  The objective of this article is to put forward several arguments between legal and unethical issues, therefore guide to conclusions that earnings management practices would risk the relationship between companies and stakeholders, the reputation of managers and accountants, and the credibility of the company.